Fixed-time cooperative guidance law with input delay for simultaneous arrival. Issue 6 (3rd June 2021) - Li, Guofei; Wu, Yunjie; Xu, Pengya
Abstract : An adaptive fixed-time cooperative guidance law is designed in this paper to intercept the manoeuvring target for simultaneous arrival. In order to improve the guidance performance, the adaptive laws are constructed to adjust the guidance gains. In particular, the convergence analysis indicates that the consensus errors converge to the origin in fixed-time interval. Furthermore, the cooperative guidance law in consideration of time-delay input is presented with some auxiliary transformations. The simulation results indicate that the missiles with proposed cooperative guidance law can hit the manoeuvring target with satisfactory performance.